ANALISIS POLA CURAH HUJAN INDONESIA BERBASIS LUARAN MODEL SIRKULASI GLOBAL (GCM) - Sinta Berlian Sipayung; Lely Qodrita Avia; Bambang Dwi Dasanto; - Sutikno (Lembaga Penerbangan dan Antariksa Nasional, 2007)
The analysis of rainfall pattern over indonesia based on the Global Circulation Model (GCM) such as the CGCM3.1(T47) and CSIRO Mk-3 for one hundred years observation (1900-2000) over three different types of Indonesia rainfall pattern has already been done. They are Lampung, Jakatra, and Kupang for the monsoon type, Ambon for the local type, and Padang and Solok for the equatorial type, repectively. Since the grid resolution of the GCM data is low relatively, we applied the Statistical Downscalling (SD) based on the Pricipal Component Regression (PCR). We found an a good agreement between both model with the rainfall in-situ measurement in between 0.6 up 0.76, except for Kupang. We found also that both model has a similar pattern comparing with the rainfall in-situ measurement. While, by applying the Principal Component Regression (PCR), we found an a good agreement also of both model than 65% with the total variability is about 90%.